The marine palynology of the Upper Cretaceous Abu Roash 'A' Member in the BED 2-3 borehole, Abu Gharadig Basin, Egypt. (2nd January 2020) - Mansour, Ahmed; Tahoun, Sameh S.; Gentzis, Thomas; Elewa, Ashraf M.T.
Abstract: This study presents a high-resolution palynological analysis for the Abu Roash 'A' Member in the hydrocarbon-rich Abu Gharadig Basin, North Western Desert, Egypt. Thirty-one rock samples, spanning the upper Coniacian to lower Campanian Abu Roash 'A' Member (180 m) from the Badr El Din (BED) 2-3 borehole, were investigated. Highly diverse and well-preserved assemblages of organic-walled dinoflagellate cysts were recorded. A total of 220 species belonging to 123 genera were identified from different levels throughout the studied succession. The marine dinoflagellate cysts represented herein by 160 species allowed three palynological assemblage zones to be recognised. These include the Satyrodinium haumuriense-Isabelidinium belfastense-Odontochitina operculata Assemblage Zone (early Campanian), Dinogymnium acuminatum-Nelsoniella aceras-Odontochitina porifera Assemblage Zone (Santonian), and Cyclonephelium filoreticulatum - Spinidinium echinoideum Assemblage Zone (late Coniacian). Approximately 17 species representing 14 dinoflagellate cyst genera are identified for the first time in the Cretaceous record of Egypt. A comparison to published palynological data from neighbouring areas reveals that several significant events are synchronous throughout the Western Desert, suggesting a common similarity of water masses. Palynofacies and palynomorph analyses of the whole samples led us to define two palynofacies assemblages, which indicate that the Abu Roash 'A' Member was deposited during a successive oscillation of sea level from distal inner to middle neritic conditions. A sequence stratigraphic framework assessment was carried out to trace the relative response of the sedimentological organic matter distribution to the changes of sea level. Four third-order transgressive–regressive sequences (SQ2–SQ5) and two incomplete transgressive–regressive sequences (SQ1 and SQ6) are constructed through the Abu Roash 'A' Member.